IMPLEMENTATION OF ECOTOURISM IN THE MANAGEMENT OF CANDIREJO HERBAL KAMPUNG SURABAYA - Sucipto Sucipto (JELAJAH: Journal of Tourism and Hospitality, 2019)
Ecotourism is a tourism activity that balances between utilization and saving (conservation). And one of the goals of the principle of ecotourism is to improve the economy of local communities. Candirejo Herbal Kampung Surabaya is one of the villages in Surabaya that promotes "green and clean" in developing it. This theme is a factor in Candirejo Herbal Village, also known as an ecotourism village. This paper focuses on applying the principles of ecotourism in Candirejo Herbal Kampung Surabaya. The purpose of this study was to determine the implementation of ecotourism and the ability of managers to implement it. For this reason, the method used to obtain information and data sources, namely interviews with management/managers, field observations to see the ecotourism implementation and using a check list to easily find out the principles of ecotourism that have been implemented. Documentation is more emphasized to the programs that have been implemented in the form of documents and to photograph something important. From the available data then a descriptive analysis is performed. Candirejo Village Administrators and the community successfully implemented the principles of ecotourism. The main key to success was that the management succeeded in realizing a clean, healthy and prosperous village community by making 7 pillars of village development and carried out cooperatively